2012
DOI: 10.1111/jam.12045
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the microbial community in industrial rye sourdough upon continuous back-slopping propagation revealed Lactobacillus helveticus as the dominant species

Abstract: Aims: To assess the structure and stability of a dominant lactic acid bacteria (LAB) population during the propagation of rye sourdough in an industrial semi-fluid production over a period of 7 months. Methods and Results: The sourdough was started from a 6-year-old freezedried sourdough originating from the same bakery. A unique microbial consortium consisting mainly of bacteria belonging to species Lactobacillus helveticus, Lactobacillus panis and Lactobacillus pontis was identified based on culture-dependen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 35 publications
0
27
0
Order By: Relevance
“…Lactobacillus panis , Lactobacillus frumenti , Lactobacillus amylolyticus and Lactobacillus acetotolerans steadily dominated industrial French sourdoughs during 10 days of propagation (Vera et al, 2012). Lactobacillus helveticus , L. panis and L. pontis were stable during long-time sourdough propagation (Viiard et al, 2012). Even in this frame, it was found that rye sourdoughs propagated at room temperature harbored different ratios of bacterial species, depending on the season of sampling (Viiard et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Lactobacillus panis , Lactobacillus frumenti , Lactobacillus amylolyticus and Lactobacillus acetotolerans steadily dominated industrial French sourdoughs during 10 days of propagation (Vera et al, 2012). Lactobacillus helveticus , L. panis and L. pontis were stable during long-time sourdough propagation (Viiard et al, 2012). Even in this frame, it was found that rye sourdoughs propagated at room temperature harbored different ratios of bacterial species, depending on the season of sampling (Viiard et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Lactobacillus helveticus dominated in the lyophilized starte and industrial semifluid sourdough samples (Viiard et al, 2013). Indeed, the stability of the sourdough microbiota at artisan, large bakery and laboratory levels depends on a number of factors, including flour microbial composition, microbial interactions, composition of flour in terms of carbohydrates and free amino acids (FAA), endogenous enzymatic activities (e.g., amylase), specific technology parameters (e.g., leavening and storage temperature, pH and redox potential, dough hydration and yield, number of sourdough refreshment steps, fermentation time between refreshments, and the use of starters and/or baker's yeast), and bakery environment (Corsetti and Settanni, 2007;G€ anzle et al, 2007;G€ anzle and Vogel, 2003;Gobbetti et al, 2005;Hammes et al, 1996;Viiard et al, 2013). Obligately heterofermentative LAB were mainly correlated with flours (e.g., Triticum durum flour), showing high levels of maltose, glucose, fructose, and FAA (Minervini et al, 2012a).…”
Section: Introductionmentioning
confidence: 99%
“…Selected strains of Lactobacillus sanfranciscensis and Lactobacillus plantarum were lost during daily back-slopping performed at laboratory level while others persisted (Scheirlinck et al, 2008(Scheirlinck et al, , 2009Siragusa et al, 2009;Minervini et al, 2010). Lactobacillus helveticus dominated in the lyophilized starte and industrial semifluid sourdough samples (Viiard et al, 2013). Indeed, the stability of the sourdough microbiota at artisan, large bakery and laboratory levels depends on a number of factors, including flour microbial composition, microbial interactions, composition of flour in terms of carbohydrates and free amino acids (FAA), endogenous enzymatic activities (e.g., amylase), specific technology parameters (e.g., leavening and storage temperature, pH and redox potential, dough hydration and yield, number of sourdough refreshment steps, fermentation time between refreshments, and the use of starters and/or baker's yeast), and bakery environment (Corsetti and Settanni, 2007;G€ anzle et al, 2007;G€ anzle and Vogel, 2003;Gobbetti et al, 2005;Hammes et al, 1996;Viiard et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…However, Lactobacillus amylovorus, Lactobacillus fermentum, Lactobacillus helveticus, Lactobacillus panis, Lactobacillus pontis, and Lactobacillus reuteri have also been identified as dominant species in rye sourdoughs [4], [6][9]. Since rye flours have a generally higher extraction rate than wheat flours [5] rye sourdoughs are characterized by higher buffering capacity compared with wheat and spelt sourdoughs but also higher concentration of mannitol and amino acids [8], [10].…”
Section: Introductionmentioning
confidence: 99%